Valuing Sustainability of Open Plan Buildings: A Case Study - Taheriattar, Reza (International Journal of Sustainable Construction Engineering and Technology, 2021)
The architecture literature acknowledges building adaptability as a means of contributing to sustainability, but falls short in valuation of this contribution. The paper demonstrates how to value sustainability of Open Plan (OP) buildings, where adaptability is deliberately incorporated in the floor plan design with future refurbishment in mind. The literature is reviewed to clarify the notion of OP building as a form of built-in adaptability and to highlight the lack of sustainability valuation of OP buildings. A case study on refurbishment of a university school building is conducted to value the adaptability. A comparative analysis of OP (built-in) adaptability and conventional (non-built-in) adaptability is carried out. Options analysis is utilized for financial valuation, in conjunction with life cycle analysis addressing social and environmental issues. The results show that the OP design is financially viable for early adaptations; and that the inclusion of environmental and social criteria in analysis improves the viability. However, the results cannot be generalized and each situation requires an individual analysis. The paper demonstrates the analysis approach and guides construction practitioners and researchers on how to value adaptable floor plans.